2012
DOI: 10.1177/0960327111433899
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cold-induced stress on liver oxidative injury during binge drinking

Abstract: The aim of our study was to evaluate the effects of cold stress on hepatic oxidative damage during binge drinking in rats. Male Wistar rats were divided into the following groups: group 1: control; group 2: ethanol-treated; group 3: stress-exposed; group 4: stress-exposed and ethanol-treated group. Oxidative and nitrosative stress parameters in the liver were determined spectrophotometrically, 12 h after treatment. Liver malondialdehyde concentration was significantly higher in group 4 when compared with group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Chronic alcohol ingestion also leads to dysregulation of physiological functions, with ramifications ranging from psychological stress and impairment to permanent pathological alterations . Finally, it has been proposed that cold temperature might increase alcohol toxicity through its effects on different oxidative mechanisms . Based on these biological and behavioral properties, it has been proposed that countries exposed to colder climates have an increased incidence of alcohol consumption and, subsequently, an amplified prevalence of alcohol‐induced organ damage, such as alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic alcohol ingestion also leads to dysregulation of physiological functions, with ramifications ranging from psychological stress and impairment to permanent pathological alterations . Finally, it has been proposed that cold temperature might increase alcohol toxicity through its effects on different oxidative mechanisms . Based on these biological and behavioral properties, it has been proposed that countries exposed to colder climates have an increased incidence of alcohol consumption and, subsequently, an amplified prevalence of alcohol‐induced organ damage, such as alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the activity of MnSOD obtained in our study is not surprising, since mitochondria are the most important organelles in ROS production [ 45 ]. Moreover, MnSOD has ability to limit the peroxynitrite formation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that CPZ increases the production of free radicals and affects the antioxidant enzyme activity in the rat liver [ 12 ]. It is known that OS in the liver is a consequence of increased production of free radicals and decreased capacity of antioxidant defense systems in hepatocytes [ 41 ]. Kupffer cells and neutrophils that infiltrate the liver represent one of the sources of ROS.…”
Section: Introductionmentioning
confidence: 99%